CARDIAC ELECTROPHYSIOLOGY AND BIOPHYSICAL ANALYSIS OF THE ECG SIGNAL - Ferangiz Izzatullayeva; Gulnoza Normukhammedova (Modern American Journals, 2025)
This article is dedicated to a thorough analysis of the electrophysiological processes of the heart and the biophysical foundations of the electrocardiogram (ECG) signal. It examines the mechanisms of generation and propagation of electrical impulses in the cardiac muscles, their role in the formation of the ECG, and the changes in ECG parameters under various pathological conditions. The article discusses modern methods for processing and analyzing ECG signals, as well as their significance in the diagnosis and monitoring of heart diseases. Based on empirical data obtained during the study and an analysis of existing literature, the role of cardiac electrophysiology and ECG in clinical practice is determined.
Keywords: Cardiac electrophysiology, Electrocardiogram (ECG), Biophysical analysis, Heart rhythm, Depolarization, Repolarization, Heart diseases, Diagnostics, Monitoring.